2009
DOI: 10.1111/j.1542-4758.2009.00335.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular conditions in hemodialysis patients may be worsened by extensive interdialytic weight gain

Abstract: The risk of death is increased for hemodialysis (HD) patients compared with age-matched healthy subjects, the main reason for this being cardiovascular conditions. This prospective study investigated whether the burden of interdialytic weight gain (IDWG) was of importance for cardiovascular end points and survival. A total of 97 HD patients were studied. The end points included death (reasons given), acute myocardial infarction, or coronary vascular intervention. The extent of ultrafiltration was measured at p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
42
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 19 publications
3
42
0
1
Order By: Relevance
“…Ultrafiltration rate (UFR) is determined by both the amount of fluid removed, which at steady state is equivalent to interdialytic weight gain (IDWG), and the time over which this fluid is removed (dialysis session length [DSL]). Prior studies have demonstrated that both shorter DSL and larger IDWG (both of which would increase UFR) are associated with increased mortality (3,(7)(8)(9)(10)(11)(12)(13)(14). However, because DSL and IDWG are highly inter-related, it is unclear whether the association of each with mortality is independent of the other.…”
Section: Introductionmentioning
confidence: 86%
“…Ultrafiltration rate (UFR) is determined by both the amount of fluid removed, which at steady state is equivalent to interdialytic weight gain (IDWG), and the time over which this fluid is removed (dialysis session length [DSL]). Prior studies have demonstrated that both shorter DSL and larger IDWG (both of which would increase UFR) are associated with increased mortality (3,(7)(8)(9)(10)(11)(12)(13)(14). However, because DSL and IDWG are highly inter-related, it is unclear whether the association of each with mortality is independent of the other.…”
Section: Introductionmentioning
confidence: 86%
“…However, it is seen as an unfit measure since dry weight can only be estimated. Nevertheless, the researchers continue to agree that IDWG should be defined as a percentage of dry weight (38,53). Furthermore, the point which defines fluid adherence is different in literature (54).…”
Section: Methods Of Measuring Adherencementioning
confidence: 99%
“…Furthermore, the point which defines fluid adherence is different in literature (54). However, research based practice states that IDWG should be less than 2.5 kg or 3.5% of dry body weight so as to reduce the excess fluid during dialysis sessions (53).…”
Section: Methods Of Measuring Adherencementioning
confidence: 99%
“…This retention is quantified as interdialytic weight gain (IDWG). High IDWG is associated with hypertension (1), intradialytic hypotension (2), and adverse cardiovascular outcomes (3,4), including increased all-cause mortality (5). It is well accepted that the degree of IDWG is influenced by dietary sodium intake (6,7), and for this reason, guidelines suggest that individuals with CKD restrict dietary sodium intake (8,9).…”
Section: Introductionmentioning
confidence: 99%